Cytological changes during certain reproductive conditions in in-vitro uterine flushing in buffaloes (Bubalus bubalis) - PROMOD, K; MAHMOOD, S; SINGH, R (The Indian Journal of Animal Reproduction, 2023)
Cytological changes during follicular, luteal phase, inactive ovarian stage and infected uterine flushings in-vitro were studied in buffalo uteri (n-54) collected from local abattoir. The overall total nucleated and epithelial cell count was significantly (P<O.O I) higher in infected uteri compared to follicular phase and inactive ovarian stage. however, differance was non-significant during luteal phase but these cells varied significantly (P<O.O J) between late-luteal phase and infected uteri. Absolute lymphocyte counts, and lymphocyte percentages varied non-significantly between two uterine horns as well as during different stages of uterine flushings, however, absolute neutrophil count and neutrophil percentage showed significant (P<O.O I) increase in the infected uteri as compared to other stages. Cytological studies cou!d be used as an adjunct to diagnose sub-clinical uterine infections. However, in-vivo study on large number of bovines, particularly in buffaloes is warrante.